Evaluation Of The Application Of Income Tax On Rent For Domestic Taxpayers After The Enactment Of Psak 73: A Case Study At The Madya Tax Service Office West Jakarta - Rico Brolin, Amos; Yulianti, Yulianti (International Journal of Science, Technology & Management, 2024)
This thesis discusses the evaluation implementation of income tax on rent for domestic taxpayers after the enactment of PSAK 73: a case study at the West Jakarta Madya Tax Service Office to ensure the gap among the current conditions that need to be followed up to provide suggestions for improvements in taxation and the Madya KPP. The research method used is qualitative with a case study approach. Respondents in this study consisted of Account Representatives and Taxpayers at the West Jakarta Madya Tax Service Office. The data used in this research consists of primary data and secondary data. Data collection was carried out through document analysis and interviews. Qualitative data analysis is carried out by involving data reduction, data presentation, and conclusion. The results of the study concluded that the implications of PSAK 73 for the tax treatment of rent for domestic taxpayers include recognizing rent as an asset and liability and increasing transparency and fairness in financial reporting. The main challenge faced by the West Jakarta Madya Tax Service Office in ensuring PPh compliance on rent after the enactment of PSAK 73 is the lack of Taxpayer understanding of the implications of this standard and the complexity that makes it challenging to fulfill tax obligations. Steps to overcome the problem of implementing income tax on rent include increasing taxpayer understanding, strengthening the audit function, collaborating with related institutions, and issuing guidance from the tax authorities.